Inulinase production by yeat Kluyveromyces marxianus - Augusto Castillo Calderón (Scientia Agropecuaria, 2010)
In this work the principal advances have been checked reached in the last twenty years, in the study of the fermentation of strains of Kluyveromyces marxianus for the production of the enzyme inulinase from inulin pure and sources of inulina and the determination of the properties and characteristics of the enzyme. With the aim of gathering and clarifying the greater knowledge of this one area, the investigation of this matter has been divided into three principal parts; substrate sources of inulin; microbial production of inulinase and characterization and properties of the inulinase. There is discussed the existing information about the microorganisms capable of producing inulinase those who have been brought by information of performance and especially the conditions of fermentation of strains of Kluyveromyces marxianus for the production of inulinase from several vegetable sources of inulin. One concludes that though it is true there exist strains of Kluyveromyces marxianus capable of producing satisfactorily inulinase, the investigation for a vegetable source of inulin economically interesting still is in process.